Generación de códigos de barras moleculares para dípteros de la familia Phoridae registrados en tres localidades del noroccidente de Ecuador - Toapanta Morocho, Ronald Daniel (2018)
The phorids, also known as humpback flies, represent possibly one of the most diverse families of diptera around the world, in addition to presenting a wide variety of behavioral habits, which gives them an important role in the ecological dynamics of ecosystems. Even so, this group has been little studied and is not considered in biodiversity inventories due mainly to the difficulty in determining its tiny species. In this sense, DNA barcodes have proven to be especially useful in the discrimination of operational taxonomic units (OTUs) in the absence of keys for species. That is why in the present work, molecular bar codes are proposed for the taxonomic identification of morphospecies of Phoridae previously classified based on their morphology, in such a way that it can contribute to the knowledge of the fauna of these diptera in the cloud forests of the Northwest of Ecuador, due to the relevance that these habitats present in the conservation field, since they are recognized among the most important hotspots in the world. In total, 52 sequences are proposed as molecular barcodes, distributed in 8 genera and 36 morphospecies, whose vouchers are deposited in the collection of the Museum of the National Polytechnic School (MEPN). The genetic analyzes, in particular the nucleotide divergences between sequences, showed a genetic distance of more than 2%, thus concluding that the mitochondrial gene CO1 is very useful for the identification of species of the family Phoridae.